THE NUTRITIONAL STATUS OF CHILDREN WITH DISABILITY AND THEIR PARENTAL FEEDING PRACTICES, FOOD SHOPPING MOTIVATION AND STRESS LEVEL AT MEALTIME DURING COVID-19 PANDEMIC - Azizi, Ain Farhani; Jaafar, Nurul Hazirah (International Journal of Allied Health Sciences, 2022)
Introduction: This study intends to identify the current nutritional status of children with disability and the pattern of their parent’s feeding practices, food shopping motivation and stress level at mealtime during the Covid-19 pandemic. Methods: Fifty-eight caregivers participated in this study by completing a validated online questionnaire survey (e.g., FFQ, HomeSTEAD, Parental Food Shopping Motivation and Parental Stress Level). The children's weight and height were measured and self-reported by the caregivers. Data were descriptively analysed. Open-ended questions about dietary and feeding practice changes were examined using thematic analysis. Results: Caregivers reported changes in the children’s daily intake, feeding practices and shopping motivations during the Covid-19 pandemic. Particularly, disruption to the routines of the children has led to an increase in their daily consumption. Caregivers were reported to change their feeding practices by being more stringent with comfort foods, implementing restrictions on unhealthy foods, and encouraging kid autonomy in food selection. As a result, many of them purchase meals that are healthier and preferred by their children. During the pandemic, food prices become the primary shopping motivation. In this study, however, caregivers reported feeling less stressed at mealtimes. Conclusions: This study provides insight into the condition of children with a disability during the pandemic. Notable changes were found in their dietary habits and parental feeding practices.